Charting Thai university students' group translation on google docs through docuviz - Nakhon Kitjaroonchai; Daron Benjamin Loo; Tantip Kitjaroonchai (National Foreign Language Resource Center, 2023)
This study sets out to investigate Thai university students' group translation of Thai texts into English in a synchronous setting. Four groups, consisting of three or four members, were involved in this study. This study examined two Thai texts translated into English, one containing tourism information and the other a crime news report. Students were given 40 minutes to translate on Google Docs, and their group translation styles were charted out through DocuViz, a visualization tool that uses color coding and number of contributions to illustrate group work. Average contributions, along with the color-coded texts, were analyzed to determine the group work styles. The study found that most groups were cooperative in their real-time translation work, in that group members worked on particular segments, with one dominant writer either editing others' contributions or translating the most. This study suggests that translation instructors consider expanding and redefining the implementation of translation tasks done in groups.